KEHIDUPAN SOSIAL MASYARAKAT SETELAH BANJIR BANDANG DI JORONG SUNGAI PANGKUA NAGARI PAKAN RABAA KECAMATAN KOTO PARIK GADANG DIATEH KABUPATEN SOLOK SELATAN - MUBARAK, HISNI AMRI; Ahmad, Drs. Ridwan; Yuherman, SP., M.Pd, Yuherman, SP., M.Pd (Pendidikan Geografi, 2014)
ABSTRACK                                                                                             This study aimed to describe the social life of the people after flash floods in river JorongPangkuaNagari Koto subdistrict Feed Rabaaskelter Tower Diateh South Solok in the social lives of everyday people after flash floods seen from : 1 ) Education of children after the flood . 2 ) public health after flash floods . 3 ) social interaction after flash floodsThis research method is descriptive , which became the study population are people who are in Jorong Pangkua River Nagari Koto subdistrict Feed Rabaaskelter Tower Diateh South Solok in the social lives of everyday people after flash floods , amounting to 350 families . Data collection using questionnaires with analysis techniques , using formulas and percentages Achievement Level Respondents ( TCR ) .Results of the study include : 1 ) education after flash floods in river JorongPangkuaNagari Koto subdistrict Feed Rabaaskelter Tower Diateh South Solok including good enough 70 71.7 % of respondents . 2 ) public health after flash floods in river JorongPangkuaNagari Koto subdistrict Feed Rabaaskelter Tower Diateh South Solok including good enough 70 67.8 % of respondents . 3 ) social interaction after flash floods in river JorongPangkuaNagari Koto subdistrict Feed Rabaaskelter Tower Diateh South Solok including both 86.5 % of the 80 respondents .